Clinical potential of mechlorethamine gel for the topical treatment of mycosis fungoides-type cutaneous T-cell lymphoma: a review on current efficacy and safety data - Liner K; Brown C; McGirt LY (Dove Medical Press, 2018)
Kendall Liner,1 Celeste Brown,2 Laura Y McGirt3 1Division of Dermatology, Medical College of Georgia at Augusta Health, Augusta, GA, USA; 2School of Medicine, University of North Carolina at Chapel Hill, Carolinas Medical Center, Charlotte, NC, USA; 3Department of Hematology/Oncology, Levine Cancer Institute, Carolinas Medical Center, Charlotte, NC, USA Abstract: Nitrogen mustard is a chemotherapeutic agent that has a well-documented safety and efficacy profile in the treatment of cutaneous T-cell lymphoma. Development of nitrogen mustard formulations and treatment regimens has been studied extensively over the last 40 years. In the last 5 years, a new gel formulation has been developed that is associated with a decrease in delayed hypersensitivity reactions. The authors in this review found that while the gel formulation may result in a decrease of allergic contact dermatitis, this advantage has been replaced by a higher number of irritant contact reactions and a decrease in complete response rate. The gel formulation has a complete response rate of 13.8%, which is a decrease in efficacy when compared to aqueous-based preparations of similar concentrations. Keywords: mycosis fungoides, nitrogen mustard, mechlorethamine gel, cutaneous T-cell lymphoma, CTCL, Valchlor®